PENGEMBANGAN MEDIA KOMIK DIGITAL DALAM PEMBELAJARAN PENDIDIKAN PANCASILA MATERI HAK DAN KEWAJIBAN PADA SISWA KELAS 3 SD NEGERI 19 PANGKALPINANG - Cyntia; Diana Pramesti; Feri Ardiansah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Pancasila Education in elementary schools still faces challenges in improving students’ understanding of rights and obligations. Observations at SD Negeri 19 Pangkalpinang revealed that students had difficulty distinguishing between rights and obligations because teachers had not used interactive media suitable for the characteristics of elementary school-aged children. Therefore, this study aims to develop a valid, effective, and practical digital comic medium to enhance students’ understanding of rights and obligations at home. This study employed a research and development (R&D) approach using the ADDIE model, which comprises the stages of analysis, design, development, implementation, and evaluation. The subjects were 39 third-grade students of SD Negeri 19 Pangkalpinang. Validation was conducted by media and material experts, followed by small-group and large- group trials to determine the practicality and effectiveness of the developed media. The data collection techniques used in this study were interviews, questionnaires and tests. Data analysis techniques include analysis of validity, practicality and potential effects. The results showed that the digital comic medium was rated highly valid by media experts (95%) and material experts (92.5%). The N-Gain test results indicated a score of 0.8051 (80%), which falls into the high and effective category. The digital comic medium achieved practicality levels of 92.5% in the small-group trial and 90% in the large-group trial, placing it in the convenient category. Therefore, the digital comic medium is effective and valuable for use in Pancasila Education learning to improve students’ understanding and learning outcomes regarding rights and obligations at home.